Effectiveness Test Application Lectora Inspire as Science Learning Media for Upgrade Concept understanding Student - Agrielsa Alphasati Sinaga; Jumadi Jumadi; Suyanta Suyanta; Nina Khaerunnisa; Sri Rejeki (Jurnal Penelitian Pendidikan IPA, 2023)
This study aim for test effectiveness application lectora inspire to understanding draft student. Research design this use design study quasi experiment with one group pretest posttest design. Sample in research this that is class VIII C with the number of 29 students and taking sample using cluster sampling technique. Instruments used is an instrument of understanding draft with material system digestion human. Data collection is carried out with use test understanding form concept _ pretest and posttest. Understanding results draft analyzed using paired sample t-test. Research results shows the average obtained of -13,428 that there is enhancement understanding draft participant educate. Then, application lectora inspire very effectiveness as learning media